Simulation on vapour compression heat pump system for rough rice drying. Issue 1 (July 2020) - Nelwan, L O; Setiawan, R P A; Yulianto, M; Irfandi,; Fachry, M; Biksono, D
Abstract: In this study, a simulation of a vapor compression heat pump system for bed drying of rough rice have been carried out for various thicknesses in the range of 20-50 cm and various drying air mass flow rates in the range of 0.06 - 0.22 kg/s-m 2 . The modelling used was grouped into two parts, i.e. the determination of temperature and humidity of the air coming out of the heat pump and the drying process of the rough rice using these air conditions. Parameters related to flow rate and energy were expressed in units of cross-sectional area of the drying bed. Simulation results showed significant differences in drying time and temperature for various thicknesses and air mass flow rates but their energy consumptions were similar. Under these conditions the drying temperature and drying time obtained ranged between 34-45°C and 8-15 hours, respectively while the specific energy consumption was relatively low i.e. in the range of 1.07-1.36 MJ/kg of evaporated water for all the scenarios tested. The specific drying air mass flow rate of 0.3 and 0.5 kg/s/m 3 did not provide significant differences in specific energy consumption. For the field applications, the selection of conditions for thickness and the appropriate air mass flow rate will depend on the user preference including the ease of mixing, drying time or energy consumption.